Sharia Marketing Management in the Digital Economy Era: A Literature Review - Annita Jannah; Nunung Nurnilasari; Rita Kusumadewi; Budi Rusdian (UIN Siber Syekh Nurjati Cirebon, 2026)
Introduction: This study reviews the development of Sharia marketing management in the digital economy era by synthesizing the existing literature on its theoretical foundations, managerial practices, digital transformation, and emerging research trends. The rapid advancement of digital technologies has reshaped marketing strategies, requiring businesses to integrate Sharia principles with innovative digital marketing approaches while maintaining ethical and value-based business practices. Methods: This study employs a literature review approach by analyzing peer-reviewed journal articles published in reputable national and international journals. Relevant studies were identified through major academic databases using predefined inclusion and exclusion criteria. The selected literature was systematically analyzed to identify dominant themes, theoretical perspectives, research methodologies, and future research opportunities. Results: The review indicates that Sharia marketing management has evolved from a value-based marketing concept into a strategic managerial framework that supports business competitiveness in the digital economy. The findings highlight that digital platforms, social media, e-commerce, and artificial intelligence have significantly influenced the implementation of Sharia marketing. Trust, transparency, ethical values, customer engagement, and digital capability consistently emerge as critical determinants of customer satisfaction, loyalty, and organizational performance. However, studies integrating digital innovation with Sharia marketing principles remain limited, indicating substantial opportunities for further investigation. Conclusion and suggestion: The literature demonstrates that effective Sharia marketing management requires the integration of Islamic ethical values with digital marketing capabilities to achieve sustainable competitive advantage. Future studies should develop comprehensive conceptual and empirical models by incorporating emerging technologies, consumer behavior, environmental sustainability, and organizational performance across different industrial contexts. This review contributes to the marketing management literature by providing a comprehensive synthesis of current knowledge and proposing future research directions for Sharia marketing in the digital economy.